A Molecular‐Dynamics Study of Size and Chirality Effects on Glass‐Transition Temperature and Ordering in Carbon Nanotube‐Polymer Composites. Issue 6 (10th October 2016) - Malagù, Marcello; Lyulin, Alexey; Benvenuti, Elena; Simone, Angelo
Abstract : Carbon nanotube (CNT) effects on the physical and structural properties of CNT‐polymer composites are investigated by means of molecular‐dynamics simulations. Results show the formation of a denser and ordered layered region of polymer matrix in the vicinity of the nanotube surface. The density and ordering of this highly ordered layer increase with the CNT diameter while chirality effects are negligible. Abstract : Molecular‐dynamics simulations of single‐walled carbon nanotubes (CNTs) embedded in a coarse‐grained amorphous monodisperse polyethylene‐like model system have been carried out. The roles of nanotube diameter and chirality on the physical and structural properties of the composite are thoroughly discussed for several CNTs with different diameter and chirality. It is shown that the glass‐transition temperature of the polymer matrix increases with the diameter of the CNT while chirality effects are negligible. A denser and ordered layered region of polymer matrix is found in the vicinity of the nanotube surface. The density and ordering of this layer increases with the CNT diameter. All simulations indicate that chirality does not affect the atomic structure of the highly ordered layer surrounding the CNTs. Despite the simplicity of the polymer model, results of this study are qualitatively comparable with those obtained from experiments and numerical simulations that consider a chemically specific polymer matrix.